2021
DOI: 10.1097/gox.0000000000003574
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated Umbilical Positioning in Abdominoplasty Using the 15/10 Rule and the “Flap Flipping” Technique

Abstract: Summary: First described by Gaudet and Morestin, abdominoplasty with umbilical preservation dates as far back as 1905. Navel position was described on the transverse axis by Rohrich, and on the median longitudinal axis, by Vernon, Baroudi and Pitanguy. The aim of this article is to validate the 15/10 rule of umbilical positioning in abdominoplasty with the “flap flipping” technique, as an intraoperative aid to simplify umbilical repositioning. Between October 2019 and March 2020, 18 consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…30 Position also changes with scars, hernias, and pregnancy in women. 15,30,31 Despite reports that BMI does not influence its location, 26 a lower umbilicus is associated with increasing BMI. 5,32 Position may also be influenced by ethnicity, 17 as well as whether the patient is high waisted or low waisted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Position also changes with scars, hernias, and pregnancy in women. 15,30,31 Despite reports that BMI does not influence its location, 26 a lower umbilicus is associated with increasing BMI. 5,32 Position may also be influenced by ethnicity, 17 as well as whether the patient is high waisted or low waisted.…”
Section: Discussionmentioning
confidence: 99%
“…1,18,45 The 15/10 rule and flap flipping technique defining an "expected zone" for umbilical positioning has been suggested, as well as an easy-to-use, intuitive yet precise, and simple guide. 15 Abhyankar et al 46 demonstrated that a 1.6:1 ratio approximating the golden ratio exists between xiphisternum-umbilicus and umbilicus-symphysis pubis; the same ratio exists between umbilicus to anterior superior iliac spine and interanterior superior iliac spine. Different ratios of similar reference measurements were, however, reported in subjects of different ethnicities; African American people have a lower lying umbilicus compared with White people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The umbilicus was exteriorized through a vertical incision through the superior flap drawn along the midline. 9 The flap was then anchored to the mons pubis, and to the scarpal cuff cephalade with three Vicryl 0 single sutures. Skin was approximated in two layers, Vicryl 2/0 spiral continuous sutures for the superficial fascia and and Vicryl 3\0 spiral continuous intra-dermal-sutures, finalized by biological glue, dressed and snugged in an abdominal binder.…”
Section: Takeawaysmentioning
confidence: 99%
“… 1 Classically, the umbilicus is transposed up to 3 cm above the iliac crest, but recent studies have challenged this concept, with the umbilicus being transposed based on the 15/10 measurement of the patients’ torso. 2 Unfortunately, not all torsos are equal, making consistency difficult. In a 2016 study, Viconti and Sagarello used the Fibonacci caliper to calculate the golden ratio (1.618) from xiphoid to abdominal scar for proper umbilical placement.…”
mentioning
confidence: 99%